2017
DOI: 10.19044/esj.2017.v13n30p496
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Yeasts Involved in Cocoa Fermentation of Six Major Cocoa-Producing Regions in Ivory Coast

Abstract: Cocoa beans (Theobroma cacao L.) are the raw material for chocolate production. Fermentation of cocoa pulp is crucial for developing chocolate flavor precursors. This fermentation is led by a succession of complex microbial communities where yeasts play key roles during the first stages of the process. In this study, we identified and analyzed the growth dynamics of yeasts involved in cocoa bean fermentation of six major cocoaproducing regions in Ivory Coast. A total of 743 yeasts were isolated, and were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Except for Z. bisporus, the presence of all the species identified in this study was frequently reported in cocoa beans fermentation [31,[35][36][37].…”
Section: Identification Of the Yeast Isolatesmentioning
confidence: 48%
“…Except for Z. bisporus, the presence of all the species identified in this study was frequently reported in cocoa beans fermentation [31,[35][36][37].…”
Section: Identification Of the Yeast Isolatesmentioning
confidence: 48%
“…Schizosaccharomyces pombe was not detected in cacao fermentations in Brazil (Camargo et al 1963 ; da Veiga Moreira et al 2013 ; Martelli and Dittmar 1961 ; Serra et al 2019 ), in Ivory coast (Koffi et al 2017 ; Koné et al 2016 ), in Indonesia (Ardhana and Fleet 2003 ), in Ghana (Jespersen et al 2005 ), in Ecuador (Papalexandratou et al 2011 ), in Cuba (Maura et al 2016 ), in Dominican Republic (Gálvez et al 2007 ) and in Ivory Coast (Ravelomanana et al 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…A rather wide yeast species diversity has been recovered from fermenting cocoa pulp-bean mass, belonging to mainly the genera Candida, Hanseniaspora, Pichia and Saccharomyces (Ardhana and Fleet 2003;Jespersen et al 2005;Nielsen et al 2005Nielsen et al , 2007aGálvez et al 2007;Daniel et al 2009;Nielsen, Jakobsen and Jespersen 2010;Papalexandratou and De Vuyst 2011;Papalexandratou et al 2011cPapalexandratou et al , 2013Papalexandratou et al , 2019Illeghems et al 2012;Pereira et al 2012Pereira et al , 2013aPereira et al , 2017Crafack et al 2013;Meersman et al 2013;Moreira et al 2013Moreira et al , 2016Moreira et al , 2017Pereira, Magalhães-Guedes and Schwan 2013b;Fleet 2014, 2015;Ramos et al 2014;Arana-Sánchez et al 2015;Batista et al 2015Batista et al , 2016Hamdouche et al 2015Hamdouche et al , 2019Koné et al 2016;Maura et al 2016;Menezes et al 2016;Miescher Schwenninger, Freimüller Leischtfeld and Gantenbein-Demarchi 2016;Samagaci et al 2016;Visintin et al 2016;Koffi et al 2017;Miguel et al 2017;Bastos et al 2018;Ho, Fleet and Zhao 2018;…”
Section: Yeasts and Labmentioning
confidence: 99%
“…The most frequently isolated yeast species are Hanseniaspora opuntiae in the beginning to the middle of the cocoa fermentation process, and Saccharomyces cerevisiae-and in some cases Pichia kudriavzevii-from the middle and later time points of the fermentation process. However, other species of Hanseniaspora and Pichia, and even diverse Candida species (and species of other genera) may occur, reflecting a great species diversity among the predominant yeast genera occurring during cocoa fermentation processes; this also reflects their various and independent origins (Jespersen et al 2005;Meersman et al 2013;Ludlow et al 2016;Maura et al 2016;Koffi et al 2017;Pereira et al 2017). All these yeast species mainly differ in acidic, ethanol and heat tolerances, explaining their successive growth and prevalence, although substrate competitiveness may not be excluded (Daniel et al 2009;Pereira et al 2012;Crafack et al 2013;Maura et al 2016;Samagaci et al 2016;Visintin et al 2016).…”
Section: Yeasts and Labmentioning
confidence: 99%